Pairing taguchi based design of experiment with response surface methodology for diesel engine performance optimization using biodiesel-magnesium oxide nanoparticles blends - Muhammad Usman Zafar; Heba G. Mohamed; Khaled Alnamasi; Abdullah M.A. Alsharif; Muhammad Nasir Bashir (PLoS ONE, 2026)
The increasing demand for diesel engines in agriculture, transportation and power generation has led to the overconsumption of fossil fuels, demanding the search for sustainable alternatives. Biodiesel has emerged as the promised alternative as it offers environmental and economic benefits. This study explores the impact of magnesium oxide (MgO) nanoparticles as an additive to the biodiesel-diesel blends on diesel engine performance. Experimental investigations were conducted on four-cylinder diesel engines under varying engine speeds, load conditions, biodiesel blends and magnesium oxide concentrations. A Taguchi L 18 orthogonal array and response surface methodology (RSM) was employed for optimal brake-specific fuel consumption (BSFC) and brake thermal efficiency (BTE). Using Taguchi paired RSM method, three input factors – Biodiesel percentage in diesel (0%, 10%, 20% v/v), engine load (25%, 50%, 75%) and MgO nanoparticles dosage of (0 g, 0.02 g, 0.04g) – were varied to assess the influence on the Brake Specific fuel consumption and Brake Thermal Efficiency. Results indicated that the addition of the MgO nanoparticles enhances combustion efficiency resulting in increase in BTE while decrease in BSFC. The maximum BTE of 23.54% was obtained at the biodiesel percentage of 12%, speed of 1200 RPM, 75% load, and 0.04g MgO. The minimum BSFC was 306.983 g/kWh was obtained at 8% biodiesel and 0.04g MgO, operating at the speed of 1200 RPM and 25% load on engine. The theoretical error in maximum BTE and minimum BSFC as compared to experimental was 1.12% and 4.6% respectively. Optimal engine performance was observed at the moderate biodiesel blends ranging between 12–16 percent with MgO at 0.04g and running between the speeds of 800–1600 RPMs. Using RSM, 7% of cost savings were obtained for the optimal cases as compared to adverse conditions in Automotive industry and 5% savings was obtained for the heavy-duty industry. These findings conclude that biodiesel blends can improve the thermal efficiency and fuel economy. The use of Taguchi L18 provides robust and low-cost procedure for the performance analysis of the diesel engine.